The Shared Set and Uniqueness of Meromorphic Functions on Annuli - Hong Yan Xu; Zhao Jun Wu (Abstract and Applied Analysis)
The purpose of this paper is to deal with the shared set and uniqueness of meromorphic functions on annulus. The set of this paper is different from the set of the paper by Cao and Deng, and our theorems are improvement of the results given by Cao and Deng.